Suprascapular nerve block in shoulder dislocation - Madeira, Sofia A. S.; Alves, Marcelo P. T.; Nunes, Catia F. C.; Rocha, Maria Ines S.; Cabaço, João D. P. (International Journal of Research in Orthopaedics, 2023)
Background: The suprascapular nerve is the main sensitive nerve of the shoulder. In 1973, the suprascapular nerve block was applied in the reduction of a series of cases of acute shoulder dislocations using mepivacaine. Barber described a method using anatomic landmarks to locate and block the suprascapular nerve. Methods: This study was approved by our Institutional Review Board and all patients signed an informed consent. We performed a prospective longitudinal study, characterized by a consecutive series of first episode of traumatic shoulder dislocation in patients over 18 years old. From July 2020 to April 2022, 50 cases were included in our study. All patients had their pain evaluated before the blockage, during the reduction and after the reduction. We used the Barber method for the blockage and the Spaso maneuver for reduction. Results: From the 50 cases, 29 were males (58%). The mean age was 58,7 years. 47 cases were anterior dislocations, 2 cases posterior dislocations and one case of luxatio erecta. The mean initial VAS was 7.5 points (minimal 4, maximum 10). The main score during the reduction maneuver was 2 points (0-5) and the main score after reduction was 0,4 (0-3). In only one case, reduction was not successful after 3 attempts, and reduction was performed under sedation. Conclusions: The suprascapular nerve block by Barber’s method proves to be a secure, effective and simple procedure to aid the shoulder dislocation reduction in the emergency room, without the need of any imaging resources.